Proceedings of the 1st International Conference on Economics, Business, Entrepreneurship, and Finance (ICEBEF 2018) 2019
DOI: 10.2991/icebef-18.2019.127
|View full text |Cite
|
Sign up to set email alerts
|

#MeTourism: How selfies affect re-visit intention in narcissistic age

Abstract: This study aims to analyze the influence of "Selfie Tourism" towards "Re-Visit Intention" moderated by "Age". This research was motivated by the changes in tourist behavior when they visit a tourist destination, where selfie has become one of the main activities to do. To answer the research questions, the author took a sample of 457 tourists in West Sumatra; Padang City, Bukittinggi City, Batusangkar City, and Payakumbuh City, which is considered to have many tourist destinations that was already shared in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…So naturally, it would be if a tourist place with a high-Value Co-Creation will encourage the tourists to re-visit the tourist destination. This research is in line with the results of the study [4,8,14,[17][18][19][20]…”
Section: The Effect Of Value Co Creation On West Sumatera's Tourist Rsupporting
confidence: 91%
“…So naturally, it would be if a tourist place with a high-Value Co-Creation will encourage the tourists to re-visit the tourist destination. This research is in line with the results of the study [4,8,14,[17][18][19][20]…”
Section: The Effect Of Value Co Creation On West Sumatera's Tourist Rsupporting
confidence: 91%
“…Based on previous research conducted by Sari & Trinanda (2020) showed that selfie promotion had a positive and significant effect on revisit interest and research conducted by Trinanda & Sari (2019) showed that selfie promotion had a positive and significant effect on revisit interest. Therefore, we posit the following hypothesis: H2.…”
Section: Selfie Promotion On Revisit Intentionmentioning
confidence: 95%
“…However, technological developments have provided smartphones or other devices that allow taking photos at any time, without limits, and without any consideration. This phenomenon also transforms the behavior of tourists who used to like sightseeing into selfie tourism [13,25]. Or even those who used to like to show "this place is beautiful", now seem more narcissistic with the tendency of "look, I'm here."…”
Section: Selfie Touristmentioning
confidence: 99%
“…In order to identify and choose tourist attractions, Generation Z also often relies on friendship networks and is heavily influenced by social media content. In fact, the virality of a tourist destination greatly influences the travel decisions made, especially for the purpose of increasing their popularity on social media [13].…”
Section: Introductionmentioning
confidence: 99%